PENGARUH REWARD AND PUNISHMENT TERHADAP KINERJA KARYAWAN ALFAMIDI KABUPATEN TANA TORAJA - Pasilong, Seprianto Ebsan Arruan; Pagiu, Chrismesi; Pundissing, Rati (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to analyze the influence of Reward and Punishment on the performance of employees at Alfamidi in Tana Toraja Regency both partially and simultaneously. The data collection procedures in this study are observation, questionnaires, and documentation. The method used in this research is a Quantitative Method utilizing Multiple Linear Regression analysis processed using SPSS 21. This research was conducted in three branches of Alfamidi located in Tana Toraja Regency, namely Alfamidi Pongtiku, Alfamidi Tritura, and Alfamidi Rukka A. Lolo, with a total population of 33 and a sample of 33 respondents. The sampling technique used by the researcher is purposive sampling. The results of the t-test calculations on the Reward variable showed t count > t table with a value of (4.457) > (2.042) and on the Punishment variable, t count > t table with a value of (4.657) > (2.042). The conclusion of this study is that Reward and Punishment have an influence on Employee Performance at Alfamidi in Tana Toraja Regency both partially and simultaneously.